Evidence that DNA damage triggers interleukin 10 cytokine production in UV-irradiated murine keratinocytes. - Nishigori, C (1996)
UV irradiation interferes with the induction of T cell-mediated immune responses, in part by causing cells in the skin to produce immunoregulatory cytokines. Recent evidence implicates UV-induced DNA damage as a trigger for the cascade of events leading to systemic immune suppression in vivo. However, to date, there has been no direct evidence linking DNA damage and cytokine production in UV-irradiated cells. Here we provide such evidence by showing that treatment of UV-irradiated murine keratinocytes in vitro with liposomal T4 endonuclease V, which accelerates the repair of cyclobutylpyrimidine dimers in these cells, inhibits their production of immunosuppressive cytokines, including interleukin 10. Application of these liposomes to murine skin in vivo also reduced the induction of interleukin 10 by UV irradiation, whereas liposomes containing heat-inactivated T4 endonuclease V were ineffective. These results support our hypothesis that unrepaired DNA damage in the skin activates the production of cytokines that down-regulate immune responses initiated at distant sites.